The Use of Drilling Techniques Integrated with Technology to Improve Students’ Vocabulary Mastery - Cahyani, Ni Putu Eka Mei; Dewi, Kadek Sintya; Mahendrayana, Gede (Journal of Educational Study, 2024)
This study aims to improve vocabulary mastery through drilling techniques integrated with technology at An Elementary School in Bali through vocabulary videos and to find out students' opinions about its application. This study used the Classroom Action Research (CAR) method. The subjects in this study were the fifth-grade class, totalling 19 students. Data were collected through vocabulary tests, observations, and interviews. Based on the results of the study, it can be concluded that the use of drilling techniques integrated with technology through vocabulary videos can improve students' vocabulary mastery. In addition, all students said that the drilling technique integrated with technology can motivate the spirit of learning and make the classroom atmosphere comfortable. Thus, it can be concluded that the use of drilling techniques integrated with technology can improve the vocabulary mastery of fifth-grade students at An Elementary School in Bali.